Collateral Vessels on 4D CTA as a Predictor of Hemorrhage Transformation After Endovascular Treatments in Patients With Acute Ischemic Stroke: A Single-Center Study - Cao, Ruoyao; Ye, Gengfan; Wang, Rui; Xu, Lei; Jiang, Yun; Wang, Guoxuan; Wang, Daming; Chen, Juan (Frontiers in Neurology, 2020)
Abstract: Objective: Although the benefits of good collateral circulation on infarct volume and outcomes have been confirmed in previous studies, few studies have investigated the relationship between hemorrhagic transformation (HT) and collateral circulation in acute ischemic stroke (AIS). This study aimed to assess whether collateral circulation is an essential factor of HT after endovascular treatments (EVTs). Methods: In total, 71 consecutive AIS patients who underwent EVTs between July 2015 and February 2019 were retrospectively studied. The correlations among HT, collateral vessels on 4D CT angiography (4D CTA), and other predictive factors for HT (e.g., National Institutes of Health Stroke Scale (NIHSS) score, age, sex, serum glucose, and atrial fibrillation history) were evaluated by logistic regression analysis. Results: The rate of hemorrhagic transformation was 42.3% (30/71) in AIS patients. Multivariate logistic regression showed that a good collateral status (OR 0.76, 95% CI 0.73–0.80) was associated with a lower risk of HT. History of atrial fibrillation (OR 2.35, 95% CI 1.96–2.82), baseline NIHSS scores (OR 2.00, 95% CI 1.72–2.32), and higher serum glucose levels (OR 1.70, 95% CI 1.57–1.85) were all independent risk factors of HT. Conclusions: Patients with poor collateral circulation are at a higher risk of HT after receiving endovascular therapy. Thus, variations in collateral circulation based on 4D CTA may be an important factor for personalized clinical treatments. In addition, high blood glucose, atrial fibrillation and the baseline NIHSS score are all important independent predictors of HT.